The Difference of Depression Score of Patients Failed Ultrafiltration Compared to Successful at Continuous Peritoneal Dialysis Patients in RSUP Dr. Sardjito Yogyakarta - Padmi Bekti Lestari; Noor Asyiqah Sofia; Iri Kuswadi (Faculty of Medicine Universitas Gadjah Mada, 2020)
Background. High mortality and morbidity in patients with Chronic Kidney Disease (CKD) are associated with psychological problems and poor quality of life. Depression is a psychological problem most often found in groups of CKD patients undergoing renal replacement therapy. Specific research that links the failure of ultrafiltration in Continuous Ambulatory Peritoneal Dialysis (CAPD) patients with depression does not yet exist today. So that further research is needed regarding this matter so that various depression intervention approaches can be carried out in the group of patients undergoing CAPD.Aims. This study aimed to determine the difference in depressive score of patients who failed ultrafiltration compared to those who did not fail in patients undergoing Continuous Ambulatory Peritoneal Dialysis (CAPD) in RSUP dr. Sardjito Yogyakarta.Method. A cross-sectional analytic study to assess differences in depressive score of CAPD patients with ultrafiltration failure compared to those who did not fail ultrafiltration in CAPD Clinic of RSUP dr. Sardjito Yogyakarta. The research subjects consisted of 41 people who fulfilled the inclusion and exclusion criteria. Depression assessment was carried out by calculating the total score of the BDI-II questionnaire and analyzing it using the Mann-Whitney method.Result. The average value of BDI-II in this study was 12 ± 8. 1. Depression scores based on BDI-II are if the score is equal to or more than 17. In this study 7 research subjects (17.1%) are depression. BDI –II values in the non-ultrafiltration failure group 10.96±7.25 and in the failed group 13.38±9.73 with p= 0.633.Conclusion. There were no significant differences in BDI-II score between groups that failed and those that did not fail ultrafiltration.